SOLIDARITAS ORGANIK ANTAR SISWA PADA KEGIATAN EKSTRAKURIKULER FUTSAL DI SMA TAMAN MULIA KUBU RAYA - Rivalina, Anastasia; Rustiyarso, Rustiyarso; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to discover about organic solidarity among students in divisions of work, collective consciousness, dominant law, and the tendency of interdependence in Futsal extracurricular in SMA Taman Mulia Kubu Raya Regency. This research used a qualitative approach with descriptive method. Techniques which are used are observation, interview, and documentation study. The instruments which used in gathering data are observation guidance, interview guidance, and documentation instrument. The result of this research showed that Organic Solidarity Among Students in Futsal extracurricular in SMA Taman Mulia Kubu Raya Regency has not run well. This was proven in students' divisions of work based on the coach?s instruction. In collective consciousness, there were students who still joined the training without permission. In Dominant law, there were students who still did against the rules. In tendency of interdependence was proven by lack of coordination among the students.Keywords: Organic Solidarity, Futsal extracurricular, Senior High School Students